If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1y + 3z = 0 Solving 4x + -1y + 3z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + -1y + y + 3z = 0 + y Combine like terms: -1y + y = 0 4x + 0 + 3z = 0 + y 4x + 3z = 0 + y Remove the zero: 4x + 3z = y Add '-3z' to each side of the equation. 4x + 3z + -3z = y + -3z Combine like terms: 3z + -3z = 0 4x + 0 = y + -3z 4x = y + -3z Divide each side by '4'. x = 0.25y + -0.75z Simplifying x = 0.25y + -0.75z
| 4a-(3a-2)=2(3a-2) | | e^2k=10 | | X+8+8-8x= | | -8x+21=3 | | (x-3)^(7/5)=128 | | 3/5÷2/3 | | 5(z+6)-2=9forz | | tan^-1(8/13) | | 5(y+1)=3 | | Abs(-7a)=28 | | sin(40)=8/x | | sin40=8/x | | F(x)=-4x^2+16 | | 6W+193=55 | | x+12=m+32 | | 8x-6x+25=35 | | 6(t-4)=3t+3 | | 8-6x+25=35 | | N^2+9n+9=0 | | 3(p+4)=2p-7 | | 5x+89=29 | | 2u+91=27 | | -7+0.25m=7 | | 0.8x+23=-25 | | 2x+24=18 | | 0.8x+23=25 | | -16a+67=3 | | 7x-35-3x=2x-13 | | 2x+24=78 | | 5c+17=2 | | -7v+81=32 | | -7v+81=7 |